Case Report: Recurrent Left Posterior Fascicular Ventricular Tachycardia in a Newborn - Lu Zhao; Lin Wu; Qu-ming Zhao; Xue-cun Liang (Frontiers Media S.A., 2021)
Left posterior fascicular ventricular tachycardia (LPFVT) is extremely rare in neonates. We described a 17-day-old girl with LPFVT who was initially misdiagnosed as supraventricular tachycardia (SVT). Eventually, she was successfully treated by amiodarone infusion followed by oral amiodarone with propranolol for 9 months, and LPFVT spontaneously resolved after a 1-year follow-up. This case report illustrated the basic principles and caveats in differential diagnosis of LPFVT in the neonatal age group. With proper diagnosis and therapy, neonatal LPFVT might regress in the first year of life.